2010
DOI: 10.1093/humupd/dmq046
|View full text |Cite
|
Sign up to set email alerts
|

What about gr/gr deletions and male infertility? Systematic review and meta-analysis

Abstract: Our meta-analysis comprising >12 000 men demonstrates that gr/gr deletions occur more frequently in infertile than control men. The association between gr/gr deletions and infertility varies according to ethnicity and geographic region, with an association reaching significance among Caucasian men, in Europe and the Western Pacific region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 44 publications
6
78
1
Order By: Relevance
“…In accordance with previous studies [13,[20][21][22], the gr/gr deletions were found to be most prevalent whereas the b1/b3 and b2/b3 deletions were of rare occurrence in the Indian population. Amongst these, the frequency of gr/gr but not b1/b3 and b2/b3 deletions was significantly higher in men with azoospermia or oligozoospermia as compared to fertile controls, none of the individuals had b2/b4 deletions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with previous studies [13,[20][21][22], the gr/gr deletions were found to be most prevalent whereas the b1/b3 and b2/b3 deletions were of rare occurrence in the Indian population. Amongst these, the frequency of gr/gr but not b1/b3 and b2/b3 deletions was significantly higher in men with azoospermia or oligozoospermia as compared to fertile controls, none of the individuals had b2/b4 deletions.…”
Section: Discussionsupporting
confidence: 92%
“…The OR for gr/gr deletions is 2.8 and 5.7 for b1/b3 deletion in infertile men. This OR is higher as compared to those reported in meta-analyses and large p<0.05 is considered as statistically significant Pregnancy rate (%) 59 (25.7) 3 (30) n are the number of men assessed in each group population-based studies [20,21,25,26] suggesting that both gr/gr and b1/b3 deletions are strong predisposing factors for male infertility in Indian population. Although gr/gr and b1/b3 deletions seem to be a risk factor for male infertility, there are normozoospermic fertile men with AZFc subdeletions, moreover b2/b3 deletions which remove almost identical amount of genetic material (and the same genes) do not predispose an individual to male infertility.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The gr/gr deletion event occurs with a relatively high frequency (3.5 %) in different Y haplotypes among men with spermatogenic failure [66]. It varies from 2.1 to 12.5 % among all cases, and from 0 to 10.2 % among normozoospermic controls [69]. In a conflicting report by Eloualid et al, [65] they have reported that gr/gr deletions occur at similar frequencies of 5.83 and 6.25 % in patient and control populations respectively, suggesting that these deletions are not associated with spermatogenic failure.…”
Section: The Azfb (P5/proximal-p1) Regionmentioning
confidence: 99%